2005
DOI: 10.1002/anie.200502243
|View full text |Cite
|
Sign up to set email alerts
|

Rate Enhancement by Ethylene in the Ru‐Catalyzed Ring‐Closing Metathesis of Enynes: Evidence for an “Ene‐then‐Yne” Pathway that Diverts through a Second Catalytic Cycle

Abstract: The ring-closing metathesis (RCM) of enynes [1!2, Eq. (1)] was first reported by Katz and Sivavec in 1985. [1]A tungsten-alkylidene precatalyst was employed and, on the basis of mechanistic studies on alkene/alkyne metathesis copolymerization, a Chauvin-type [2] mechanism involving an "yne-then-ene" sequence was proposed (Scheme 1, cycle A).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 37 publications
(18 reference statements)
1
45
0
Order By: Relevance
“…Mechanistic studies: In enyne metathesis, the mechanism [6b] at play is still a matter of debate. The question asked is whether an "ene-then-yne" [34] or a "yne-then-ene" pathway is involved. [35] In order to shed more light on the matter, we considered both pathways with the dienyne substrates shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistic studies: In enyne metathesis, the mechanism [6b] at play is still a matter of debate. The question asked is whether an "ene-then-yne" [34] or a "yne-then-ene" pathway is involved. [35] In order to shed more light on the matter, we considered both pathways with the dienyne substrates shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…First, an elegant mechanistic study was conducted by Lloyd-Jones. 54 In this investigation, the authors showed that 13 C-labeled ethylene produced vinyl carbene turnover, showing that ethylene turns over the vinyl carbene by what the authors termed a 'second cycle,' via reaction with the auxiliary alkene, ethylene. In other words, ethylene assists the turnover of the intermediate vinyl carbene (see Scheme 3, where R¼CH 2 ).…”
Section: Role Of Ethylene In Ring-closing Enyne Metathesis (Mori's Comentioning
confidence: 97%
“…A mechanism involving an ene-thenyne metathesis of tethered enynes was supported by labeling experiments [1261]. Ruthenium-catalyzed ene-yne RCM reactions of cyclopropane substituted 1,6-enynes forming either bicyclic or monocyclic compounds depending on the catalyst (Eq.…”
Section: Metathesis Reactionsmentioning
confidence: 99%